Comparıson Of Lower And Upper Extremıty Y Balance Test Scores Of Some Team And Indıvıdual Adolescent Athletes (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to determine the relationships between the Y Balance Test (YBT) upper and lower extremity balance scores of judo, taekwondo, basketball and volleyball players. A total of 46 athletes, including judo (12), taekwondo (10), basketball (10) and volleyball (12), participated in the study. Participants were evaluated with lower extremity Y balance test (LE YBT) and upper extremity Y balance test (UE YBT). The collected data were analyzed with the SPSS 22 program using an independent t test. As a result of the analyzes, it was seen that all of the upper extremity Y Balance Test and Arm length data of taekwondo, judo, basketball and volleyball players were statistically significant according to the branches, and all the lower extremity Y Balance Test and Chimney length data were statistically significant according to the branches P<0,01. As a result, It can be said that lower extremity Y Balance Test and upper extremity Y Balance Test values of basketball and volleyball players, where limb length is at the forefront, are better than judo and taekwondo branches, which are individual double combat sports. This result can be attributed to the limitation of physical structure due to the fact that judo and taekwondo branches are welterweight sports and limitation of the physical activity, and the physical capacity of basketball and volleyball sports to create an advantage in the competition.